KARAKTERISTIK PARA PEMIMPIN YANG DIIDOLAKAN MASA KINI DAN MASA DEPAN PADA ORGANISASI - Ni Wayan Mujiati (Forum Manajemen STIMI Handayani Denpasar, 2017)
Leader is a person who actively make plans, coordinate, doing experiments and leadingthe work to achieve the goal together. Leader and leadership is the nature of humanity, since thehuman there. At the moment leader and leadership have been there. The discussion of leaders andleadership in general explain how to be a good leader, types and character in accordance withany leadership and the ability possessed by a leader in order to be a leader who idolized on thepresent and the future of organization. Edmonds’ research (1974) in Sobry Sutikno (2014) presentthere are 25 characteristics need to be owned by the leaders in order to become a leader whoidolized both the present and the future of the organization will be presented in this paper.